Pengaruh Pelaksanaan Program Keselamatan Kesehatan Kerja (K3)Terhadap Produktivitas Kerja Karyawan - Prawiranegara, Raden Indra; Tjahjawati, Sri Surjani (Jurnal Riset Bisnis dan Investasi, 2015)
Increased employee productivity and occupational health safety is the main aspect to be taken by each company. Some of the problems is a workplace that is not feasible, this can lead to hazards that can arise in the workplace itself, health workers are low, and decreased work productivity of employees. Occupational health and safety program is an effort to improve employee productivity. This study aims to determine the effect of occupational health safety to employee productivity at PT Pindad (Persero). In this study, occupational health safety is the independent variable (X) and employee productivity is the dependent variable (Y). This research is a quantitative research used descriptive method and survey method. By type and method of the study, data analysis used is descriptive analysis, a classic assumption test, regression test, correlation and hypothesis testing. This study Table Krejcie to determine the sample. By using krejcie table can be seen what will be the sample of respondents. The sample in this study were 140 respondents who are employees of PT Pindad (Persero). Results of simple linear regression, obtained by the equation Y = 33.867 + 0.209 X with R-Square of 0.603. It shows that the variable quality of work life of 60.3% impact on work productivity, while labor productivity by 39.7% influenced by other things such as work attitude, leadership, control, management of labor productivity and efficiency so that is not explained in this study. Therefore, it can be seen that there is significant health salvation to employee productivity at PT Pindad (Persero).